Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Jinheung Electric Indonesia - Yolanda, Karmila; Rismayadi, Budi; Sumarni, Neni (Peneliti.net, 2024)
This study aims to examine and analyze the influence of work motivation and discipline on the performance of employees of PT. Jinheung Electric Indonesia. Data collection was carried out by distributing questionnaires with a total sample size of 100 respondents and using a quantitative descriptive approach. Therefore, the data analysis used is statistical analysis in the form of multiple linear regression tests. The results of this study indicate that partially and simultaneously, the variables of motivation and discipline affect the performance of employees at PT. Jinheung Electric Indonesia. This is evidenced by the results of the simultaneous test (F test) and the results of the partial test (t test), which also show the significant values of the two independent variables that support the hypothesis. Therefore, the test results of this study state that there is a simultaneous influence between the variables of motivation and work discipline on the performance of PT. Jinheung Electric Indonesia. As for the implications for companies, the research results can be used as material for consideration to improve employee performance; this shows a positive value, where motivation and work discipline must be carried out properly in order to create better performance results.